2008 IEEE Symposium on Computational Intelligence and Games 2008
DOI: 10.1109/cig.2008.5035636
|View full text |Cite
|
Sign up to set email alerts
|

Interactively evolved modular neural networks for game agent control

Abstract: Abstract-As the realism in games continues to increase, through improvements in graphics and 3D engines, more focus is placed on the behavior of the simulated agents that inhabit the simulated worlds. The agents in modern video games must become more life-like in order to seem to belong in the environments they are portrayed in. Many modern artificial intelligence approaches achieve a high level of realism but this is accomplished through significant developer time spent scripting the behaviors of the Non-Play… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Previous research by Whiteson and Stone in combining NEAT and Q-learning has shown promising results [138,139]. These methods have been applied with some success to shooters [89] and racing games [13].…”
Section: B Comparing and Combining Evolution With Other Learning Metmentioning
confidence: 99%
“…Previous research by Whiteson and Stone in combining NEAT and Q-learning has shown promising results [138,139]. These methods have been applied with some success to shooters [89] and racing games [13].…”
Section: B Comparing and Combining Evolution With Other Learning Metmentioning
confidence: 99%
“…However, when the effect of mutations was constrained by a hand-designed modular network structure separating the two subproblems, evolution was able to find optimal neural controllers consistently. In the literature there are other examples where researchers relied on manual decomposition of the control problem by subdividing the control architectures into a predefined number of modules, based on a priori knowledge of the problem (e.g., [18], [19], [20]). However, it is not always obvious how control problems should be decomposed into tractable sub-problems [21].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it has partially/indirectly supported an additional Masters thesis 21 . The REU research has also led to the publication with former undergraduate participants of 5 conference papers [22][23][24][25][26] (with undergraduates Hoover, Beck, Garcia, Cardona, Alexander, Ahmed, Sparks and Miguez) and 1 journal paper 27 (with undergraduate Hoover). Also, it has indirectly and subsequently aided in the research presented in 9 additional conferences and 2 journals, which we do not list here.…”
Section: A Research Outcomesmentioning
confidence: 99%